John Newsom-Davis: clinician-scientist and so much more. - Vincent, A (2011)
John Newsom-Davis was born in 1932 and died, aged 74, in 2007. After national service in the Royal Air Force, he read Natural Sciences at Cambridge. Following clinical studies at the Middlesex Hospital, he began research into respiratory neurophysiology with Tom Sears at the National Hospital, Queen Square, in London, and spent 1 year with Fred Plum at Cornell University in New York. After neurology specialist training at Queen Square, he became the director of the Batten Unit, continuing his interest in respiratory physiology. There he began to work on myasthenia gravis in collaboration with Ricardo Miledi at University College London and in 1978, after performing the first studies on plasma exchange in that disease, he established a myasthenia gravis research group at the Royal Free Hospital. There he investigated the role of the thymus in this disease and demonstrated an autoimmune basis for the Lambert Eaton myasthenic syndrome and 'seronegative' myasthenia. He was awarded the first Medical Research Council Clinical Research Professorship in 1979 but moved to Oxford in 1987 when he was elected Action Research Professor of Neurology. While at Oxford, he continued to run a very successful multidisciplinary group, researched further into the thymic abnormalities and cellular immunology of myasthenia, identified antibody-mediated mechanisms in acquired neuromyotonia, and began the molecular work that identified the genetic basis for many forms of congenital myasthenic syndrome. Meanwhile, he was also involved in university and college governance and contributed widely to the Medical Research Council, government committees, research charities and the Association of British Neurologists. Among many honours, he was elected Fellow of the Royal Society in 1991, appointed Commander of the British Empire in 1996 and made a Foreign Associate Member of the Institute of Medicine of the United States in 2001. Nearing and following retirement from Oxford, where he continued to see patients with myasthenia, he was the President of the Association of British Neurologists and Editor of Brain, and led a National Institutes of Health-funded international trial of thymectomy.